Restructuring of the Port Elizabeth Hospital Complex: a perspective from the planned change management approach - Qwesha, Babalwa (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
The research objectives which underpin this study were threefold. Firstly was to analyze the Port Elizabeth Hospital Complex (PEHC) restructuring process from a planned changed management perspective in particular the three stage model of Lewin (1951) which include unfreezing the current equilibrium, moving to a new position and refreezing in the new position. Secondly was to analyze how unforeseen circumstances were dealt with. Thirdly was to analyse the setting of objectives and measurements of targets to monitor progress. The study is based on the restructuring that took place in the PEHC which was called "Rationalization" . The research indicates that the development and implementation of the rationalization cannot be understood from the perspective of the three stage model of Lewin (1951). The conclusion was based on the manager's perceptions of their analysis of the restructuring in the light of the theory of the three stage model of Lewin (1951). The study has shown that: · Rationalisation began by gathering information on the shortcomings of the structure of the three hospitals, but did not understand the degree of readiness to change. · The timescales for achieving rationalization were not clearly defined. · It was driven from the top with clear objectives and no timescales. · There was no structure that prepared the employees to go through the process of rationalisation. · There was lack of capacity of middle managers to respond to the workers in an encouraging way. · Rationalisation sub-committees had limited time to meet with employees at the sectional level. · External stakeholder involvement was not mobilized to its full potential. · Rationalisation was not an open process that involved both formal and informal employees. · Budget constraints and staff shortages were not informed by the restructuring needs. · Workers did not feel secure about the current and future work practises. · There was no feeling that the change will be beneficial to their wellbeing and to the organisation's goals and mission · There was no monitoring and evaluation put in place to track progress. · There was centralisation of even the most basic administrative functions. The study seems to imply that the restructuring in the PEHC bears no resemblance to the Lewin (1951) planned change model and therefore cannot be understood from the perspective of this model. Given the initiative to rationalize, the PEHC management can learn from the model of Lewin (1951) planned change.
Keywords: Hospitals -- Administration -- South Africa -- Port Elizabeth; Organizational change -- Management -- South Africa -- Case studies